Pharmacotherapy : a pathophysiologic approach - DiPiro, Joseph T. (New York : McGraw-Hill Medical, 2011)
"The most comprehensive, widely used, and evidence-based pharmacotherapy text available Hailed by Doody's Review Service as "one of the best in pharmacy" Pharmacotherapy: A Pathophysiologic Approach is unmatched in its ability to help students develop a mastery of evidence-based medicine for optimum patient outcomes. The eighth edition will feature the addition of SI units throughout and an increased number of global examples and clinical questions. Features Unparalleled guidance in the development of pharmaceutical care plans Full-color presentation Key Concepts in each chapter Critical Presentation boxes summarize common disease signs and symptoms Clinical Controversies boxes examin complicated issues you face when providing drug therapy NEW material added to the online learning center EXPANDED evidence-based recommendations EXPANDED coverage of timely issues such as palliative care and pain medicine Therapeutic recommendations in each disease-specific chapter"--Provided by publisher.
Machine generated contents note: Section 1: Foundation IssuesSection Editor: L. Michael Posey1.Pharmacoeconomics: Principles, Methods, and Applications (Web-only) Lisa A. Sanchez 2.Health Outcomes and Quality of Life (Web-only) Stephen Joel Coons 3. Evidence-Based Medicine (Web-only) Elaine Chiquette and L. Michael Posey 4. Documentation of Pharmacy Services (Web-only) George E. MacKinnon, III and Neil J. MacKinnon 5.Clinical Pharmacokinetics and Pharmacodynamics Larry A. Bauer 6.Pharmacogenetics Larisa H. Cavallari and Y. W. Francis Lam 7. Pediatrics Milap C. Nahata and Carol Taketomo 8. Geriatrics Catherine I. Starner, Shelly L. Gray, David R. P. Guay, Emily R. Hajjar, Steven M. Handler, and Joseph T. Hanlon 9. Pharmacoepidemiology Andy Stergachis, Thomas K. Hazlet, and Denise Boudreau 10. Clinical Toxicology Peter A. Chyka 11. Emergency Preparedness: Identification and Management of Biological Exposures (Web-only) Colleen M. Terriff, Jason E. Brouillard, Lisa T. Costanigro, and Jessica S. Gruber 12. Emergency Preparedness: Identification and Management of Chemical and Radiological Exposures (Web-only) Greene Shepherd and Richard B. Schwartz Section 2: Cardiovascular Disorders Section Editor: Robert L. Talbert 13. Cardiovascular Testing Robert Chilton and Robert L. Talbert 14. Cardiopulmonary Resuscitation Jeffrey F. Barletta and Jeffrey L. Wilt 15. Hypertension Joseph J. Saseen and Eric J. MacLaughlin 16. Heart Failure Robert B. Parker, Jo E. Rodgers, and Larisa H. Cavallari 17. Ischemic Heart Disease Robert L. Talbert 18. Acute Coronary Syndromes Sarah A. Spinler and Simon de Denus 19. The Arrhythmias Cynthia A. Sanoski, Marieke Dekker Schoen, and Jerry L. Bauman 20. Diastolic Heart Failure and the Cardiomyopathies 21. Venous Thromboembolism Stuart T. Haines, Daniel M. Witt, and Edith A. Nutescu 22. Stroke Susan C. Fagan, David C. Hess 23. Hyperlipidemia Robert L. Talbert 24. Peripheral Arterial Disease Barbara J. Hoeben and Robert L. Talbert 25. Use of Vasopressors and Inotropes in the Pharmacotherapy of Shock Robert MacLaren, Maria I. Rudis, and Joseph F. Dasta 26. Hypovolemic ShockBrian L. Erstad Section 3: Respiratory Disorders Section Editor: Robert L. Talbert 27. Introduction to Pulmonary Function Testing Jay I. Peters and Stephanie M. Levine
Keywords: Chemotherapy; Physiology, Pathological; Drug Therapy